RANCANG BANGUN MODUL TRAINER KIT MATA KULIAH SISTEM KENDALI+LAB BERBASIS INTERNET OF THINGS (IoT) - Hernandi, William; Rahardjo, Pratolo; Alit Swamardika, Ida Bagus; Divayana, Yoga; Oka Saputra, Komang (Program Studi Teknik Elektro UNUD, 2024)
Along with the development of technology, control systems can now control various devices using smartphones connected to the internet remotely (Internet of Things). In order to have a good understanding of this field, universities have a very important role as an education institution. One of them is Udayana University through the Control System + Lab Course in the Independent Campus Learning Curriculum. This study aims to design an IoT-based Lab + Control System Trainer Kit Module using DevKit ESP32. The designed system includes an IoT-based DC motor control system using an L298N motor driver, an IoT-based water cooling control system using a DS18B20 temperature sensor, and an IoT-based water level control system using an HC-SR04 ultrasonic sensor. The system will be controlled through an application that has been created and installed on a smartphone connected to the internet so that it can be tested and analyzed to draw conclusions.